PEMANFAATAN JENIS -JENIS MEDIA BK DI SEKOLAH PADA PEMBELAJARAN DARING - Ni Made Dwi Narita Kusumawardani; Ni Komang Sri Yuliastini; Dwi Sri Rahayu; Ni Ketut Kusuma Umbarini Sari (Widyadari : Jurnal Pendidikan, 2022)
The purpose of making this article is to find out how to apply the types of BK media to students at school. Learning activities can be done anywhere and in general learning activities are carried out in schools. This means that the goal in an activity is to change behavior, regardless of the existence of a skill, knowledge, or attitude that can cover all aspects of the organism or person. In learning activities there are media that are used as tools for complementary learning facilities. BK media itself has two types that can be used, such as electronic media and non-electronic media. The method used in this study is a literature review that collects data from various literature sources related to the theme of this article, including several related studies that have been carried out previously. The results of this study indicate that there are many types of guidance and counseling media that can be used to help students better understand the learning given at school. This BK media can also be used online and offline and has a positive impact on students. The positive impact can be in the form of increasing student creativity, increasing student critical thinking and also increasing student understanding. Besides for students, BK media itself has many positive benefits for all teachers/teachers.